The measurement of dynamic young's modulus in composite laminates - Cheng, Y. F.
The suitability of the resonance-free vibration method and the impact method in the measuring of the dynamic Young's modulus in oron-aluminium, fibreglass-epoxy and boron-epoxy laminates has been studied. In the vibration method, the concept of equivalent length was developed. Using the equivalent length, the vibration method gave dynamic values of(Ed)t , and (Ed)22 which were practically the same as the static values. The impact method gave a dynamic value of Young's modulus noticeably lower than the static value. The difference between (Ed)~l from impact and those from vibration increases with the ratio of Ef/Er.--thus showing the effect of the dispersion of stress wave velocity. In addition, (Ed)22 from impact was always lower than those from vibration and was apparently not related to the ratio of Ef/Em. It is concluded that, in the dynamic characterisation of fibre-reinforced laminate materials, the resonance-free vibration method is preferable to the impact method.